PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP PEMAHAMAN MATERI HAK DAN KEWAJIBAN PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SD - Adelia Cherlyana; Ulwan Syafrudin; Roy Kembar Habibi; Muhammad Nurwahidin (STKIP Subang, 2026)
The issue of low understanding of the rights and obligations of IV grade elementary school students is the main focus of this study. The purpose of this study was to determine the effect of the Problem-Based Learning model on the understanding of rights and obligations in the Pancasila Education subject in the IV grade of elementary school. This type of research is quantitative, using a quasi-experimental method with a non-equivalent control group design. The population of this study was IV grade students at SD Negeri 2 Banarjoyo, with samples taken using purposive sampling techniques. Class IV A served as the control class, and class IV B served as the experimental class. The data collection techniques used in this study were tests and non-tests. From hypothesis testing using a simple linear regression test, it was obtained t_hitung = 4,259 with n = 20 for α = 0,05 obtained t_tabel = 2,101, so that t_hitung > t_tabel (4,259 > 2,101). Furthermore, with a significance value of 0.000 < 0.05, it means that the PBL model has an effect on the understanding of rights and obligations, with an effect of 50.2% based on the R Square test. This proves that there is an increase in understanding of the material on rights and obligations in the Pancasila Education subject in IV grade elementary school using the problem-based learning model.